2005
DOI: 10.1186/cc3520
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction The present article reports our experience with high-frequency oscillatory ventilation (HFOV) in pediatric patients who deteriorated on conventional mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…As the debate about the value of HFOV in pediatric respiratory failure refractory to conventional means continues, the greater the need to share different experiences from different areas of the world to try to add to our understanding of this unresolved issue. We were able to demonstrate the clear value of HFOV rescue therapy in improving both oxygenation and ventilation as has been described by others from different areas of the world in our study population [1][2][3][4][5]. The majority of our patients had DAD as a pathophysiology, which explained the failure of both oxygenation and ventilation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As the debate about the value of HFOV in pediatric respiratory failure refractory to conventional means continues, the greater the need to share different experiences from different areas of the world to try to add to our understanding of this unresolved issue. We were able to demonstrate the clear value of HFOV rescue therapy in improving both oxygenation and ventilation as has been described by others from different areas of the world in our study population [1][2][3][4][5]. The majority of our patients had DAD as a pathophysiology, which explained the failure of both oxygenation and ventilation.…”
Section: Discussionsupporting
confidence: 82%
“…By using HFOV, we recruit diseased lung and improve oxygenation, and to some degree ventilation, by constantly distension using high mean airway pressure (MAP) with tidal volume less than anatomic dead space. Several studies in medical literature have suggested more improvement, mainly in oxygenation and also in ventilation, in patients managed with HFOV when compared to conventional mechanical ventilation (CMV) [1][2][3][4][5]. Despite the wide use in all age groups and many success stories with this mode of HFOV, some newly published studies have described contradicting results.…”
Section: Introductionmentioning
confidence: 99%
“…This was observed in 92% of the patients in this case series. In children, an effective CO 2 removal has been demonstrated by HFOV [ 25 ]. Several studies in adults, however, found PaCO 2 increasing or unchanged during HFOV [ 12 , 13 , 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Slee-Wijffels and colleagues [ 7 ], in a retrospective single centre study, reported on the use of HFOV in paediatric patients ( n = 53) who deteriorated on CMV. They observed that HFOV rescue therapy was associated with a high overall survival (64%).…”
Section: Mechanical Ventilationmentioning
confidence: 99%